2022
DOI: 10.1111/vop.12978
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of phacoemulsification and aspiration in 182 eyes: Visual outcomes and CDE‐predictive value

Abstract: Objective To determine the effect of cumulative dissipated energy (CDE) on complications and visual outcome following cataract surgery in dogs. Animals studied Records of 182 canine eyes that had undergone cataract surgery. Procedures Retrospective medical record review was conducted on dogs that underwent unilateral or bilateral elective cataract surgery by a single surgeon. Preoperative variables such as age, cataract duration, and pre‐existing conditions were recorded. Intraoperative variables such as intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Total intraocular fluid volume was not specifically reported in the medical records of our population but has been correlated with endothelial cell loss, 88,89 increased central corneal thickness immediately postoperatively in dogs, 12 and recently with the eventual development of corneal ulcerations in a canine study 6 . Postoperative stromal and subepithelial edema may compromise the health and integrity of the corneal epithelium and represent factors that could predispose to IPCE.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Total intraocular fluid volume was not specifically reported in the medical records of our population but has been correlated with endothelial cell loss, 88,89 increased central corneal thickness immediately postoperatively in dogs, 12 and recently with the eventual development of corneal ulcerations in a canine study 6 . Postoperative stromal and subepithelial edema may compromise the health and integrity of the corneal epithelium and represent factors that could predispose to IPCE.…”
Section: Discussionmentioning
confidence: 89%
“…Both values are normalized, accounting for different phacoemulsification settings between patients; 82 and CDE is a value adjusted for longitudinal and torsional ultrasound delivered by modern phacoemulsification handpieces, a value now reported at surgery completion by many machines. A recent veterinary study found increased CDE to be predictive of glaucoma and vision loss in dogs undergoing routine phacoemulsification 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations